Epidermal Microfluidic Electrochemical Detection System: Enhanced Sweat Sampling and Metabolite Detection - Martín, Aida; Kim, Jayoung; Kurniawan, Jonas F; Sempionatto, Juliane R; Moreto, Jose R; Tang, Guangda; Campbell, Alan S; Shin, Andrew; Lee, Min Yul; Liu, Xiaofeng; Wang, Joseph (ACS sensors, 2017)
Despite tremendous recent efforts, noninvasive sweat monitoring is still far from delivering its early analytical promise. Here, we describe a flexible epidermal microfluidic detection platform fabricated through hybridization of lithographic and screen-printed technologies, for efficient and fast sweat sampling and continuous, real-time electrochemical monitoring of glucose and lactate levels. This soft, skin-mounted device judiciously merges lab-on-a-chip and electrochemical detection technologies, integrated with a miniaturized flexible electronic board for real-time wireless data transmission to a mobile device. Modeling of the device design and sweat flow conditions allowed optimization of the sampling process and the microchannel layout for achieving attractive fluid dynamics and rapid filling of the detection reservoir (within 8 min from starting exercise). The wearable microdevice thus enabled efficient natural sweat pumping to the electrochemical detection chamber containing the enzyme-modified electrode transducers. The fabricated device can be easily mounted on the epidermis without hindrance to the wearer and displays resiliency against continuous mechanical deformation expected from such epidermal wear. Amperometric biosensing of lactate and glucose from the rapidly generated sweat, using the corresponding immobilized oxidase enzymes, was wirelessly monitored during cycling activity of different healthy subjects. This ability to monitor sweat glucose levels introduces new possibilities for effective diabetes management, while similar lactate monitoring paves the way for new wearable fitness applications. The new epidermal microfluidic electrochemical detection strategy represents an attractive alternative to recently reported colorimetric sweat-monitoring methods, and hence holds considerable promise for practical fitness or health monitoring applications.